Combined Experimental and Computational Approach for the Vibrational Characteristics and Theoretical Evaluation of Binding Activities and ADME Descriptors of 2, 6-Di-tert-butyl-p-cresol. (21st April 2022) - Anbu, V.; Karthick, T.; Vijayalakshmi, K. A.
Abstract: A crystalline sample of multipotent molecule "2, 6-di- tert -butyl- p -cresol" (DBPC) was characterized by FT-IR, FT-Raman and its spectroscopic signatures were analyzed using density functional theory (DFT) computations. The weaker intermolecular interactions such as π-π, alkyl-alkyl, π-alkyl in the extended molecular framework were analyzed by Quantum topological atoms in molecule approach. The conformational analysis of the structure and the optimized geometrical parameters of the minimum energy conformer were discussed in detail. The excitation energies corresponding to one electron transition from various HOMO and LUMO energy levels were predicted using DFT. The second-order perturbation approach has been implemented to determine interaction energies between the molecular species. The predicted nonlinear optical (NLO) properties (second-order hyperpolarizabilities) suggest that DBPC can act as NLO materials. Since it has been already found as an anti-oxidant agent, an attempt was performed to find its active binding sites on phase II metabolism isoenzyme. The adsorption, distribution, metabolism and excretion descriptors were predicted to evaluate its drug-likeness. Also, the Swiss BOİLED-Egg model indicates that DBPC can be passively permeated through the blood-brain barrier and is predicted not to be effluated from the central nervous system by p-glycoprotein (PGP¯).